Assessing the Adaptability of Vegetable Amaranth (Amaranthus viridis L.) for Cultivation in North Eastern India - Bora, G. C.; Gogoi, S.; Bora, P. K.; Rahman, S.; Deka, J. (Agricultural Sciences: Techniques and Innovations Vol. 1, 2025)
Amaranth (Amaranthus viridis L.) is an important leafy vegetable crop of Assam and North East India. Both leaves and whole plants are used for consumption purposes. Grain amaranthus is also grown in many countries, including India. The study aimed to evaluate systematically the promising lines of the plant Amaranth as a whole. Therefore, the present investigation was undertaken at Assam Agricultural University, Jorhat, which has resulted in two promising varieties of amaranthus, the performance and characteristics of which are presented in this paper. Sixteen accessions of vegetable amaranth (Amaranthus viridis L.) were collected from different locations of the state of Assam and North East. The accessions were tested for leaf and plant yield and component characters under different breeding trials. They were evaluated consecutively for three years in the Dept. of Horticulture, AAU, Jorhat in station trials. The observations were recorded on different quantitative and qualitative characteristics as per the descriptor of the NBPGR. Standard statistical analysis for yield and component characters was done following Panse and Sukhatme. The promising varieties were tested in zonal and AICRP (VC) trials. For further confirmation of the results, the varieties were tested in On-Farm trials also. The accessions viz., Am-1, Am-2, Am-3, Am-4, Am-5, Am-6, Am-7, Am-8, Am-9, Am-10, Am-11, Am-12, Am-13 (Boga Morisa), Am-14 (Ranga Morisa), Am-15 and Am-16 were tested in zonal trials covering UBVZ (Upper Brahmaputra valley zone), NBPZ (North Bank Plains zone) and LBVZ (Lower Brahmaputra valley zone) also. In these trials, among all genotypes, JorAm-1(Shyamali) and JorAm-2 (Rodali) were found to be the best for leaf and plant yield and other component characters. The AICRP trials conducted throughout the country exhibited an average plant yield of 147.93 q/ha in JorAm-1 and 143.27 q/ha in JorAm-2 with 25 – 30% yield increase over the best check variety. Shyamali was a green leaf variety whereas Rodali was a purplish variety. The edible leaves were getting ready for plucking 30 – 35 days after sowing. Both of them were found to be tolerant with 5% incidence of leaf spots and aphids. They have been recommended in the Zonal Research Committee Meeting (ZREAC), and Annual Technical Committee Meeting (ATCM) held at Assam Agricultural University (AAU), Jorhat for release in the state of Assam. In view of consumer preference and taste, the varieties are spreading very fast and gaining popularity throughout the entire NE state. Based on the results mentioned above, the varieties JorAm-1 and JorAm-2 have been recommended. Accordingly, proposals in the name of Shyamali (JorAm-1) and Rodali (JorAm-2) have already been submitted for their release. Preliminary reports have been published in different literature at different times about these varieties. Considering yield performance and other desirable characteristics, extensive cultivation of these varieties may be done in better-performing states.